Persistent hypersomnia following repetitive mild experimental traumatic brain injury: Roles of chronic stress and sex differences. Issue 6 (9th January 2023) - Portillo, Edwin; Zi, Xiaomei; Kim, Yeonho; Tucker, Laura B.; Fu, Amanda; Miller, Lauren A.; Valenzuela, Krystal S.; Sullivan, Genevieve M.; Gauff, Amina K.; Yu, Fengshan; Radomski, Kryslaine L.; McCabe, Joseph T.; et al.
Abstract: Traumatic brain injury (TBI) is often more complicated than a single head injury. An extreme example of this point may be military service members who experience a spectrum of exposures over a prolonged period under stressful conditions. Understanding the effects of complex exposures can inform evaluation and care to prevent persistent symptoms. We designed a longitudinal series of non‐invasive procedures in adult mice to evaluate the effects of prolonged mild stress and head injury exposures. We assessed anxiety, depression, and sleep–wake dysfunction as symptoms that impact long‐term outcomes after mild TBI. Unpredictable chronic mild stress (UCMS) was generated from a varied sequence of environmental stressors distributed within each of 21 days. Subsequently, mice received a mild blast combined with closed‐head mild TBI on 5 days at 24‐h intervals. In males and females, UCMS induced anxiety without depressive behavior. A major finding was reproducible sleep–wake dysfunction through 6‐ to 12‐month time points in male mice that received UCMS with repetitive blast plus TBI events, or surprisingly after just UCMS alone. Specifically, male mice exhibited hypersomnia with increased sleep during the active/dark phase and fragmentation of longer wake bouts. Sleep–wake dysfunction was not found with TBI events alone, and hypersomnia was not found in females under any conditions. These results identify prolonged stress and sex differences as important considerations for sleep–wake dysfunction. Furthermore, this reproducible hypersomnia with impaired wakefulness is similar to the excessive daytime sleepiness reported in patients, including patients with TBI, which warrants further clinical screening, care, and treatment development. Abstract : Traumatic brain injury (TBI) is experienced during complex conditions. As an extreme example of this point, military personnel have experienced multiple blast and impact head injury exposures under stressful conditions. This complexity may confound attribution of common TBI symptoms. Our longitudinal modeling studies identify stress exposures as inducing sleep–wake dysfunction.